2012
DOI: 10.1007/s10616-012-9469-7
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of electrochemically reduced water on matrix metalloproteinase-2 activities and in vitro invasion of human fibrosarcoma HT1080 cells

Abstract: It has been demonstrated that hydrogen peroxide (H(2)O(2)) is directly associated with elevated matrix metalloproteinase-2 (MMP-2) expression in several cell lines. Electrochemically reduced water (ERW), produced near the cathode during electrolysis, and scavenges intracellular H(2)O(2) in human fibrosarcoma HT1080 cells. RT-PCR and zymography analyses revealed that when HT1080 cells were treated with ERW, the gene expression of MMP-2 and membrane type 1 MMP and activation of MMP-2 was repressed, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…Further studies with N1E-115 cells demonstrated that the suppressive effect of ERW stemmed from its ROS scavenging ability. This finding is in accordance with the previous reports obtained from pancreatic β -cell HIT-T15 cells [ 15 , 19 ], human lung carcinoma A549 cells [ 41 ], HT1080 tumor cells [ 24 ], and diabetic db/db mice [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further studies with N1E-115 cells demonstrated that the suppressive effect of ERW stemmed from its ROS scavenging ability. This finding is in accordance with the previous reports obtained from pancreatic β -cell HIT-T15 cells [ 15 , 19 ], human lung carcinoma A549 cells [ 41 ], HT1080 tumor cells [ 24 ], and diabetic db/db mice [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…ERW contains a high concentration of dissolved hydrogen (0.4–0.9 ppm) and a small amount of platinum nanoparticles (Pt nps, 0.1–2.5 ppb), both of which exhibit ROS-scavenging ability [ 11 , 16 , 17 ]. Neutralized ERW has been shown to exhibit H 2 O 2 -scavenging activity which is correlated with protection of DNA [ 18 , 19 ] and carbon tetrachloride induced liver damage [ 20 ], lifespan extension of Caenorhabditis elegans [ 16 , 21 ], alloxan-induced type 1 diabetes [ 15 , 19 ], hemodialysis-induced oxidative stress during end-stage renal disease [ 22 , 23 ], and inhibitory effects of HT1080 tumor cell invasion [ 24 ]. ERW, in combination with glutathione, induced human leukemia HL-60 apoptotic cell death whereas a cytotoxic effect was not observed in normal peripheral blood mononuclear cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…5C and D). The suppressive effect of the MMP2/MMP9 inhibitor II in cell invasion was also observed in A549 cells, H-Ras-12V-expressing H322Fyn cells and HT1080 cells, of which invasion was reported to be regulated by MMP2 and MMP9 (33,34) (Supplementary Fig. S8).…”
Section: Oncogenic Ras Signaling Activates Sfks and Promotes Cdcp1-dementioning
confidence: 69%
“…According to reports, internalized PtNPs are estimated to be approximately 8,000 particles per cell when using 2 nm PtNPs at 10 mg/l; this demonstrates strong ROS scavenging activity when these PtNPs are added to the cells. By simple calculation, the internalized PtNPs will be 8 particles per cell when 10 −3 mg/l PtNPs is added to the cells [14,50]. Therefore, it is unlikely that such a small number of internalized PtNPs could directly exert strong ROS scavenging ability in the present study.…”
Section: Several Antioxidative Protein Mrnas Are Upregulated By Ptnpsmentioning
confidence: 84%